(3GdJfHjg Ydi GdCSHGH GdJi ChLHJ GdGNJdGa Hjf GdeSdejf aj BQGFges - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe CHh eMeO , YHO Gddg Hf eMeO GdMeO ddg eSHZ GdfYe heShZ GdbSe s
(3BNQgG (B:s
(3hCfG GSJZaQ Gddg ef Rdd Ef cGf YQV hCSCdg YhfkG Ydi eG JYHO Hg haQV dGQH ZjQg BNQg hcGf GdaQGZ efg s
(3GdfGSN Jhai SfI (B775 (3hgh UGMH GdLhGgQ GdeVjI ai WHbGJ GdMfajIs
(3cJH HNW Cgd GdfbW ajg CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3CUhd abg (B39) s
Keywords: (3CUhd Gdabgs